2019
DOI: 10.1371/journal.pone.0222388
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of rocker shoes on plantar aponeurosis strain in patients with plantar fasciitis and healthy controls

Abstract: Plantar fasciitis is a frequently occurring overuse injury of the foot. Shoes with a stiff rocker profile are a commonly prescribed treatment modality used to alleviate complaints associated with plantar fasciitis. In rocker shoes the apex position was moved proximally as compared to normal shoes, limiting the progression of the ground reaction forces (GRF) and peak plantarflexion moments during gait. A stiff sole minimizes dorsiflexion of the toes. The aim of this study was to investigate whether the biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Rocker-soled shoes are such a design that has been functionally designed for walking and running. Previous studies have shown that these shoes can cause significant changes in lower extremity biomechanics [1][2][3][4][5] . MBT shoes (Masai Barefoot Technology, Switzerland), which were probably the first rocker-soled shoes, were invented by observing the walking patterns of the Masai people.…”
mentioning
confidence: 99%
“…Rocker-soled shoes are such a design that has been functionally designed for walking and running. Previous studies have shown that these shoes can cause significant changes in lower extremity biomechanics [1][2][3][4][5] . MBT shoes (Masai Barefoot Technology, Switzerland), which were probably the first rocker-soled shoes, were invented by observing the walking patterns of the Masai people.…”
mentioning
confidence: 99%
“…). Furthermore, it has been reported that gait with common footwear reduces ankle stability(Ramanathan et al, 2011), increases plantar aponeurosis length(Lin et al, 2013), minimises peak Achilles tendon force, and reduces first metatarsophalangeal joint dorsiflexion angle(Greve et al, 2019). The gait with running footwear showed the same ankle dorsiflexion as the barefoot gait(Louey & Sangeux, 2016), while the gait with military boots demonstrated a restricted range of ankle mobility (Schulze et al, 2014).…”
mentioning
confidence: 99%